Human Adenovirus, Mesophilic Bacteria and Fungi in Puppies’ Food Marketed in Bulk in Southern Brazil - dos Santos Carvalho, João Cléber; Antunes Eisen, Ana Karolina; Fetzner Pucci, Caroline do Amaral; Demoliner, Meriane; Picoli, Simone Ulrich; Spilki, Fernando Rosado; Henzel, Andréia (Acta Scientiae Veterinariae, 2019)
Background: The Brazilian domestic canine population are the second largest in the world and their feeding means 0.4% of the Brazilian gross domestic product. For maintaining the quality of the food, the companies use worldwide standards for technical prevention and control of contaminants and biological conservation. The packaging is part of this process, since it provides a barrier between food and environment. However, in Brazil, packagings are often opened in retail stores for bulk marketing. The objectives of this work were to develop a methodology to detect viruses in foods and to analyze the bacterial and fungal contamination in puppies’ food sold in bulk in Ivoti and Estância Velha, cities in Southern Brazil. Materials & Methods & Results: Twenty samples collected between September and October 2016 were analyzed for most probable number of coliforms, Salmonella sp., mesophilic aerobic bacteria and yeast/mold following the regulation of the Brazilian Ministry of Agriculture, Livestock and Food Supply guidelines. They were also tested for Human Mastadenovirus C (HAdV), Canine Mastadenovirus A (CAdV), and Carnivore Protoparvovirus 1 (CPV) genomes. Viral analysis were performed by polymerase chain reaction (PCR) detection. During the collection of the samples hygienic-sanitary conditions, storage of feeds, animals’ access, dog grooming, and veterinary care were considered to evaluate the conditions of each store. A pilot study was carried out using one food sample marketed in bulk and one sample from the original package (closed package) and testing them for bacterial and fungal contamination for standardizing viral detection. Ten grams of food from the original package were mixed with 90 mL of Eagles’ Minimal Essential Medium (E-MEM) in 100 mL sterile bottles. These bottles were kept in room temperature and shaken for 60 min. Subsequently, aliquots were obtained by sequentially diluting the sample (10-2 to 10-4). All final specimens contained 10 mL and each diluted sample was spiked with HAdV-C prototype viral strain (AdV5). A standard solution of HAdV-C was diluted from 3.6x106TCID50mL, (50% tissue culture infective dose) to 3.6x103 TCID50mL, and DNA extraction was performed. Nested-PCR targeting AdV DNApol was performed to detect adenoviruses from different hosts. AdV-positive samples were submitted to nucleotide sequencing and phylogenetic analysis. Specific PCRs were also carried out for CAdV and CPV. Mesophilic aerobic bacteria were detected in all samples and Aspergillus sp. was found in five samples, among which one sample was co-infected with Penicillium sp. One sample was positive for AdV, which was identified as HAdV by sequencing; while coliforms and Salmonella sp. were not detected. Discussion: The presence of fungi with mycotoxigenic potential, such as Aspergillus sp. and Penicillium sp. represents a threat for canines, due to toxins that may persist for a long period even after the fungus is not viable. Moreover, dogs seem to be more susceptible to the effects of the toxins, which is probably because of low glutathione s-transferase activity. Some species of Penicillium sp. genus may produce ocrathoxin A, which nephrotoxic and immunosuppressive effects in dogs are widely reported. Mesophilic bacteria were detected in all samples (at 104 CFU/g) and considered harmless. The detection of human viruses points to the presence of anthropic contamination; on the other hand, ingestion of contaminated feed, even if it is by a heterologous species, turns the dogs into carriers of the virus. In addition, manipulation of those feeds by children who share the same space with dogs can result in gastroenteritis episodes.